Femmes et francophones Pour un dépassement des marginalités dans les constructions genrées - Barthelmebs, Hélène (Romanica Silesiana)
Women and French-speaking Writers. Move Beyond Marginalities in Gendered Constructions Writing, for female authors, and above all for French-speaking writers, is a transgressive act. The double marginalization provided by these peripheral statuses, when compared to the emblematic figure of the “French writer”, leads to the question of the construction of “decentered” identities. By focusing exclusively on works from (the) Francophone literature (those by Assia Djebar, Anne Hébert and Alice Rivaz), this study of feminine identities and women’s literary constructions analyzes parallel themes inherent to literary female characters: they are simultaneously the reflection of social realities and an ideological deconstruction. The paper also examines linguistic and stylistic features involved in the delineation of feminine writing. French-speaking works generally propose the destruction of frozen identities, reflecting the phenomena more or less marked by transculturation, (such as the deconstruction of literary genres, and the subversion of the cultural heritage of the “dominant”). There are numerous similarities between the situation of the colonized and of women, namely, the stereotypes that transform them into a subculture in which they are seen as objects rather than subjects. Key words: Gender Studies, francophone literatures, woman’s writing, 20th century literature, norm, transgression.